The Effect of MWCNT-Oil Impregnation of Sintered Components on Their Wear and Corrosion Resistance - Abdelfadeel, Maha Khaled (AUC Knowledge Fountain, 2026)
Powder Metallurgy (PM) offers an advantageous route for manufacturing complex and near net-shape components. Their inherent interconnected porosity that promotes the action of self lubrication compromises their structural integrity by creating pathways for corrosion and excessive wear. This research investigates the efficacy of Multi-Walled Carbon Nanotubes (MWCNTs) as a nano additive within the impregnating base oil (SN-150 base oil). An experimental matrix was designed to evaluate the influence of MWCNTs with different concentrations of 0.05, 0.1, and 0.2 wt.% and ultrasonic dispersion with varying sonication times of 30 and 60 minutes on the tribological and electrochemical performance of sintered steel self-lubricating bushings. The study confirms that the use of MWCNTs -based nanofluids can successfully penetrate the porous sintered steel structures, achieving oil content exceeding 19% across all specimens. In tribological performances, lower concentrations of MWCNTs proved superior, where specimens impregnated with nanofluid (NF) containing 0.05 wt.% MWCNTs, sonicated for 60 minutes, exhibited approximately 90% reduction in wear rate, resulting in a value of 0.45mg/km compared to reference specimen achieving 4.7mg/km, and a stabilized coefficient of friction, induced by the rolling-effect mechanism of the dispersed MWCNTs. On the other hand, electrochemical polarization test method revealed that with increasing MWCNTs concentrations, corrosion resistance increases. NF, containing 0.2 wt.% MWCNTs, and sonicated for 60 minutes, exhibited an inhibition efficiency of approximately 82% and reduced the corrosion rate to 0.18 mm/year, compared to the reference specimen which demonstrated 1.02 mm/year. The resulting findings establish MWCNTs-NF as an impregnation lubricant a transformative approach for PM components, optimizing their mechanical properties and environmental resistance to meet industrial application requirements.